2011
DOI: 10.1186/1472-6963-11-353
|View full text |Cite
|
Sign up to set email alerts
|

Earlier surgical intervention in congenital heart disease results in better outcome and resource utilization

Abstract: BackgroundCongenital heart disease (CHD) accounts for a major proportion of disease in the pediatric age group. The objective of the study was to estimate the cost of illness associated with CHD pre, intra and postoperatively; among patients referred to a tertiary care hospital in Karachi, Pakistan. This is the first study conducted to estimate the cost of managing CHD in Pakistan.MethodsA prevalence based cost of illness study design was used to estimate the cost of cardiac surgery (corrective & palliative) f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
12
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 13 publications
1
12
0
Order By: Relevance
“…We found that among our CHD subjects, 20% had cyanotic heart disease and 80% had acyanotic heart disease, similar to results reported in both local and international studies. [2][3][4][5][6][7][8][9][10][11][12] The ASD and VSD were the most common lesions in our study subjects. Of our CHD subjects, we noted that 103/235 (43.8%) had ASD, which was similar to results from previous studies in neighboring Pakistan, 32.1% at the Punjab Institute of Cardiology (PIC), Lahore, 39.9% at the National Institute of Cardiology Karachi, and 38.16% at the Siddique Sadiq Memorial Trust Hospital, Gujranwala.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…We found that among our CHD subjects, 20% had cyanotic heart disease and 80% had acyanotic heart disease, similar to results reported in both local and international studies. [2][3][4][5][6][7][8][9][10][11][12] The ASD and VSD were the most common lesions in our study subjects. Of our CHD subjects, we noted that 103/235 (43.8%) had ASD, which was similar to results from previous studies in neighboring Pakistan, 32.1% at the Punjab Institute of Cardiology (PIC), Lahore, 39.9% at the National Institute of Cardiology Karachi, and 38.16% at the Siddique Sadiq Memorial Trust Hospital, Gujranwala.…”
Section: Discussionmentioning
confidence: 99%
“…1 Congenital heart disease is a high contributor to the overall burden of pediatric cardiovascular diseases. 2 In developing countries like Afghanistan with very limited health facilities and poor access to the health centers, having a child with cardiovascular defects often results in social and economic problems that affect the entire family. 2 In the Western world, the incidence of CHD was reported to be 8/1,000 live births.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…[1][2][3][4] Hence, early diagnosis of fetal CHD is of great signifi cance for timely postnatal surgical intervention or termination of pregnancy. [5,6] Accordingly, novel biomarkers for the improvement of efficiency and accuracy in the diagnosis of fetal CHD are needed in combination with conventional fetal echocardiography. [7,8] In the new era of non-invasive prenatal tests, potential biomarkers such as microRNAs, [9,10] proteins, [11] and the merging fetal cells [12] in maternal circulation that will cause minimum risk to fetus are easily accepted.…”
Section: Introductionmentioning
confidence: 99%